EFFECTIVE STRATEGIES APPLIED IN ENGLISH SPEAKING CLASS (A Case Study of 8 Graders of MTs Muhammadiyah 1 Ciputat) - Ainunnisa, Dinda Putri; Zaitun, Zaitun; Hadi, Muhammad Sofian (Universitas Muhammadiyah Palembang, 2021)
This study was aimed at portraying teachers’ strategies in teaching speaking to students of Junior High School and recognizing these students’ responses toward those strategies by involving two English teachers and a class of 22 students. This research tried to find out whether or not the strategies used by the teachers in teaching speaking were effective. This was a case study which applied qualitative method. The instruments used to collect the data were interviews and questionnaire. Two English teachers of that school became the informants of the interview, while the questionnaire was distributed to the students. The results showed that in teaching speaking in English class, the strategies used by the teachers were discussion and storytelling. By implementing these two strategies, the students were able to use English easier, became more active and were able to receive the material well. The results of the questionnaire revealed that 73.18% students were interested in English learning, 76.59% students preferred storytelling strategy and 73.41% students thought that discussion strategy was more enjoyable for them.